Cumulative average triglyceride glucose-waist height index and incident cardiovascular disease in middle-aged and older adults: A nationwide cohort study from the china health and retirement longitudinal study - Liang Zeng; Li Zhao; Jixiang Wan; Linji Li; Yiping Guo (PLoS ONE, 2026)
Background Insulin resistance (IR) is a significant risk factor for cardiovascular disease (CVD), yet practical biomarkers for long-term IR assessment are limited. The triglyceride glucose-waist-to-height ratio (TyG-WHtR) index, integrating lipid/glucose metabolism and central obesity, offers a novel composite marker. We investigated the association between cumulative average TyG-WHtR and incident CVD in middle-aged and older adults. Methods This prospective cohort study utilized data from the China Health and Retirement Longitudinal Study (CHARLS). Participants aged ≥45 years without baseline CVD were included (n = 5,328). Cumulative average TyG-WHtR was calculated from Wave 1 (2011) and Wave 3 (2015) using the formula: [TyG × WHtR], where TyG = ln[(TG mg/dL × FBG mg/dL)/2] and WHtR = waist circumference (cm)/height (cm). Incident CVD was defined as new self-reported physician-diagnosed heart disease/stroke or active treatment during follow-up. Multivariable logistic regression and restricted cubic spline models assessed associations, adjusting for demographics, lifestyle, cardiometabolic risk factors, and comorbidities. Results Over 4 years, 568 (10.7%) participants developed CVD. Higher cumulative average TyG-WHtR quartiles showed progressively increased CVD incidence (Q1: 7.4%, Q4: 13.3%; P-trend<0.001). After full adjustment, participants in Q2–Q4 had significantly higher CVD risk versus Q1 (Q2: OR=1.451, 95% CI: 1.095–1.928; Q3: OR=1.427, 1.066–1.917; Q4: OR=1.436, 1.035–2.000). Each 1-SD increase in TyG-WHtR was associated with a 18.3% higher CVD risk (OR=1.183, 95% CI: 1.052–1.332). A linear dose-response relationship was observed (P for overall = 0.018, P for nonlinear = 0.409), particularly for heart disease (P for overall = 0.010). Results remained consistent across subgroups (age, sex, smoking, comorbidities) and sensitivity analyses. Conclusions Cumulative average TyG-WHtR independently predicts incident CVD in middle-aged and older Chinese adults. The cumulative average TyG-WHtR index may serve as a potential practical tool for early identification of individuals at elevated cardiovascular risk.